Analisis Kesalahan Frasa pada Teks Berita dalam Detik.Com Edisi Februari 2025 - Bili, Ruben Akter; Kami, Kanisius; Gena, Engel Bertha Halena (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the form of phrase errors in news texts in the February 2025 edition of Detik.Com. The type of research used is a type of descriptive research. The data in this study are quotes that contain phrase errors. The source of data in this study is the text of the news in the February 2025 edition of Deik.Com. The data collection technique in this study is to read news texts and record phrase errors. The data analysis technique in the study is extralingual matching. Clarify errors at the syntactic level especially in the field of phrases and draw conclusions from phrase errors. Based on the results of the study on phrase errors in news texts in Detik.Com, researchers found 24 phrase error data, with details: 9 types of preposition errors that are not applied, namely; in 18, to the consumer, to the person, to the couple, in the middle, in the friday edition, to the country, in the day, and to Patrick Kluivert,1 a type of improper wording error namely; 14 Types of errors in the use of excessive or redundant elements, namely; last year 2022, last Sunday afternoon (01/02), April 2025, February 5, 2025, 2025 edition, 2025 edition, 2025 tomorrow, immediately after, three children, last Thursday (14/2/2025), last February 2, 2025. February 13, 2025, U-20 2025 and U-20 2025.